Analisis Sekuritisasi Presiden Donald Trump Dalam Kebijakan Protecting The Nation From Foreign Terrorist Entry Into The United States (2016-2019) - Marsanda Aulia; Hermini Susiatiningsih; Satwika Paramasatya (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
In responding to the issue of immigrants, the United States has come up with a controversial policy. Donald Trump brought up the Protecting The Nation From Foreign Terrorist Entry Into The United States policy to limit the entry of Muslim immigrants into the United States. Donald Trump securitizes the issue by giving a speech act that forms a threat construction in the issue of Muslim immigrants. Until finally the policy that was rejected was accepted by the community and enforced. It is interesting to study how state leaders shape the construction of an issue so that they can get support from the community. This study will reveal this through a key question regarding